Feeding of Bait to Snail Lymnaea acuminata and Their Effect on Certain Enzyme in the Nervous Tissue. (4th December 2012) - Kumar, Pradeep; Singh, V. K.; Singh, D. K.
Abstract : Fascioliasis, a snail-borne parasitic zoonosis, has been recognized for a long time because of its major veterinary and human impact. Different Bait formulations were fed to the snail Lymnaea acuminata in clear glass aquaria having diameter of 30 cm. Snail attractant containing bait formulations was prepared from different binary combination (1 : 1 ratio) of carbohydrates (glucose, starch 10 mM) and amino acid (methionine, histidine 10 mM) in 100 ml of 2% agar solution + sublethal (20% and 60% of 24 h and 96 h LC50 ) doses of different molluscicides (eugenol, ferulic acid, umbelliferone, and limonene). Snails fed on bait containing sub-lethal concentration of different molluscicides and the snail attractant, causing a significant inhibition in alkaline phosphatase (ALP) and acetylcholinesterase (AChE) activity in the nervous tissue of the vector snail L. acuminata . Maximum inhibition in ALP (20% of control) and AChE (49.49% of control) activity was observed in the nervous tissue of the L. acuminata exposed to 60% of 96 h LC50 of eugenol in the bait pellets containing starch + histidine, starch + methionine, respectively.